Sztuka kulinarna jako nowy przemysł kreatywny - Oszup-Rawicz, Małgorzata (Załącznik Kulturoznawczy, 2023)
The authoress puts up a thesis that certain ways of preparing, serving and consuming food have the qualities of classifying them as belonging to the sphere of art. Going further in her analysis places culinary amongst the creative industries, in the area where art meets economics. The authoress reachesout to various sources and presents a wide variety of theories, opinions as well as facts that support her thesis.